(untitled) (Prithvi Academic Journal, 2019)
Climate change is one of the most complex and crucial issues in the world. It has impacted environmental, social, and economic sectors of our planet. Unsurprisingly, Nepal is not immune to climate change. In fact, it is one of the most susceptible countries to climate change. One of the most impacted variables in Nepal due to climate change is the maximum temperature. The rate of change of temperature per year, in Nepal is ever-increasing. This paper examines the temperature trend and how it has affected environmental, social, and economic sustainability of Kaski District in Nepal. The paper utilizes the maximum temperature trend of Kaski District during 1970-2018. The monthly minimum and maximum temperatures are obtained from the Department of Hydrology and Meteorology (DHM). The study is done based on the data obtained from Pokhara Airport and Lumle stations. The paper uses three statistical tools alongside descriptive statistics to analyze the data. First, the Man-Kendall test is used to figure out the trend of temperature. Second, Sen’s slope is used to find the magnitude of a trend. Third, the Time series model has been used for forecasting temperature trends. Finally, SPSS and R software were used to calculate the results. The trend of maximum temperature has been significantly increased in Kaski District. The maximum temperature in Kaski during 1970-2018, recorded, was 24.99°C in 2005 and was closely followed by 24.66°C temperature in 2010. The average maximum temperature during the 1970-2018 period was 23.49°C. The maximum variation of maximum temperature during 1970-2018 was in 1992 with a standard deviation of 5.94°C. The minimum temperature during 1970-2018 was 21.12°C in 1978 and was closely followed by 22.19°C in 1997. There is an increasing trend of maximum temperature in Kaski District. In addition, the trend of maximum temperature is higher and faster after 1998 in Kaski District of Western Nepal during 1970-2018.